Employment mobility and returns to technical and vocational training: Empirical evidence for Tanzania - Vincent Leyaro; Cornel Joseph (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
This paper examines the employment mobility and returns to technical and vocational training (TVET) relative to general education in Tanzania, using data from the 2014 Integrated Labour Force Survey (ILFS). The results show that TVET training facilitates individual easy transition into employment. As it has been shown, both in descriptive statistics and regression results, that technical, on job training, vocational and apprenticeship training are particularly important in acquiring formal employment. The results further show that, though the returns to general education (GED) and TVET are positive and statistically significant, on average those with TVET trainings are earning relatively less than those with general education, implying lower returns to TVET graduates compared to general education graduates. The descriptive statistics confirm this by showing that, in Tanzania, workers with university degree earns twice of those with technical training and three times those with vocational training. Clearly, two implications stand out here: one, technical and vocational training are very instrumental in addressing the rising youth unemployment; and two, to make it attractive to parents and students governments across the region has to work towards raising the returns to TVET.
Keywords: J24; J31; 330; employment mobility; returns; TVET; Tanzania